Improvise interface design of UTHM academic online resources e-learning system (author) / Azizul Zamri Muhamed Amin - Muhamed Amin, Azizul Zamri (2013)
Education is very important especially in these challenging times. Various technologies day by day are growing, also the current educational technology. If in the past the traditional delivery of education there should be a lecturer in front and students listened to what the lecturer presented orally. Now keeping pace with technology education where knowledge is delivered not only in accordance with the timetable in the classroom, but can also be delivered on-line and accessible regardless of time and place restrictions call as blended learning techniques. Blended learning is used to deliver knowledge among technology websites, videos, interactive cd, multimedia equipment and many more. The availability of this technology has triggered a variety of learning techniques such as blended learning. There are so many systems that can can support learning techniques process such as Online Academic Online Resources (AUTHOR), an e-learning system used by UTHM. A learning management system must be developed with creativity and innovative features in terms of interface design and system capability to ensure the effectiveness of the system for lecturers and students. Therefore the purpose of this study is to find out why lecturers and students at the Faculty Of Computer Science and Information Technology, UTHM are not fully utilized this e-learning system (AUTHOR). The findings shows that through the development of a workable prototype with improvise interface design using blended learning concept can be applied in this e-learning system (AUTHOR). Hopefully with this improvised interface design will attract the lecturers and students more to fully utilized this system in the future.